2015
DOI: 10.1088/0953-8984/27/19/194105
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-responsive alginate capsules

Abstract: Upon incorporation of magnetic nanoparticles (mNPs) into gels, composite materials called ferrogels are obtained. These magneto-responsive systems have a wide range of potential applications including switches and sensors as well as drug delivery systems. In this article, we focus on the properties of calcium alginate capsules, which are widely used as carrier systems in medicine and technology. We studied the incorporation of different kinds of mNPs in matrix capsules and in the core and the shell of hollow p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…On the other hand, magnetic deformation of capsules filled with magnetic particles was reported in Refs. 23,24; these magnetic particles, however, aggregated and did not remain in a stable ferrofluid state. The aim of this work is a reliable capsule system, into which a stable ferrofluid can be loaded at high concentra-tion such that it can strongly deform in magnetic fields, which is important for possible applications of capsules as actuators, switches, or valves.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…On the other hand, magnetic deformation of capsules filled with magnetic particles was reported in Refs. 23,24; these magnetic particles, however, aggregated and did not remain in a stable ferrofluid state. The aim of this work is a reliable capsule system, into which a stable ferrofluid can be loaded at high concentra-tion such that it can strongly deform in magnetic fields, which is important for possible applications of capsules as actuators, switches, or valves.…”
Section: Introductionmentioning
confidence: 98%
“…Magnetic nanoparticles, which are sterically stabilized by amphiphiles such as lauric acid or electrostatically stabilized, destabilize and flocculate in the presence of calcium ions if both ions and nanoparticles are in the aqueous phase in the liquid core of the capsule. 24 To reduce this effect oil-soluble magnetic particles can be used, which are encapsulated in an oil in water emulsion, where calcium is solved in the aqueous emulsion phase. 26 In previous work, we showed that encapsulation of a stable ferrofluid is possible with this technique and that a significant deformation in magnetic fields can be achieved.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…where d D is the Caps displacement, F is the measured force, h is the membrane thickness, which is imported as a fixed value of 0.20 mm, r is the radius of the Caps and υ s is the surface Poisson ratio for which a value of 1/2 was assumed for the alginate hydrogel [25]. The permeability of mm-CaSA-Caps was measured by the diffusion of glucose from bulk solution into intra-hollow Caps.…”
Section: Capsule Characterizationmentioning
confidence: 99%
“…Owing to its biodegradability, non-toxicity, non-immunogenicity, ease of processing, and low cost, alginate has been broadly employed across a variety of medical devices [11]. Capsules of alginate ranging in size from tens of nanometers [12] to several millimeters [13] can be implanted in humans with minimal side effects [14]. As a result, alginate capsules incorporating a broad array of payloads have been deployed for a variety of purposes, including drug delivery, cell encapsulation, bone regeneration, wound healing, and regenerative medicine [15].…”
Section: Introductionmentioning
confidence: 99%